Let the other number be represented by y.
Now, since the sum of the two numbers is 44, we have that:
![x+y=44](https://img.qammunity.org/2023/formulas/mathematics/college/4y4j4poaydgk8n0rcxkq86wsr05rqr6orp.png)
Now, we simply make y the subject of the relation by subtracting x from both sides of the equality sign, as follows:
![\begin{gathered} x+y=44 \\ \Rightarrow x+y-x=44-x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dkidubgmajma8y0blvanfm4tp1vl01qvhz.png)
![\Rightarrow y=44-x](https://img.qammunity.org/2023/formulas/mathematics/college/6yb3mpk76gcvtaunti4ii4jzik4zll6xk4.png)
Therefore, the other number is given by:
![44-x](https://img.qammunity.org/2023/formulas/mathematics/college/d0m4664zr99cp70m5znlu7rhgvp7u1qepr.png)